Investigating the solutions of empowering of women against poverty / Investigando as soluções de empoderamento das mulheres contra a pobreza - Papinejad, Masumeh; Bagheri, Shahla; Papinejad, Shahrbanu (Revista de Direito da Cidade, 2018)
Abstract The poverty of women and the amount of their mastery over the economic sources, have been the center of a lot of negotiations and discussions and the wary of joining some of the women to the group of "poorest poor" and their frustration of the advantages of development after second world war have led to proposing different approaches for helping them. One of the approaches is empowering the women. The documentary methodology and analysis of studies are used for doing the research about this topic. In fact, the present research is from descriptive-analytical approach researches in terms of gathering the data. In this way, first some study cases about empowering the women is investigated in this research, then required definitions are provided about some concepts like poverty, empowering, and women empowerment and the theory of women empowerment is discussed. In following, it is purposed to the importance of empowering the women against the poverty be investigated with an analytical approach and finally, after analytical review of approaches and strategies of women empowerment which are used in different countries and societies, the five main approaches in this field got investigated. These approaches are information and computing technology (ICT), microfinance, manufacturing cooperatives, Suitable social capital and human development. It is indicated analytically that the success of each of these approaches depends on paying attention to others. Keywords: Women, Women’s empowerment, solution, Poverty Resumo A pobreza das mulheres e a quantidade de seu domínio sobre as fontes econômicas têm sido o centro de muitas negociações e discussões e o cuidado de unir algumas das mulheres ao grupo de "pobres mais pobres" e sua frustração das vantagens de desenvolvimento após a Segunda Guerra Mundial levou a se propor diferentes abordagens para ajudá-las. Uma das abordagens é capacitar as mulheres. A metodologia documental e a análise de estudos são utilizadas para a pesquisa sobre o tema. De fato, a presente pesquisa adota abordagem descritivo-analítica em termos de coleta de dados. Desta forma, primeiro alguns casos de estudo sobre o empoderamento das mulheres são investigados nesta pesquisa, então são necessárias definições sobre alguns conceitos como pobreza, empoderamento e empoderamento das mulheres e a teoria do empoderamento das mulheres é discutida. A seguir, pretende-se investigar a importância do empoderamento das mulheres contra a pobreza com uma abordagem analítica e, finalmente, após a análise analítica das abordagens e estratégias de empoderamento das mulheres que são usadas em diferentes países e sociedades, as cinco principais abordagens do campo foram investigadas. Essas abordagens são tecnologia da informação e computação (TIC), microfinanças, cooperativas de manufatura, capital social adequado e desenvolvimento humano. É indicado analiticamente que o sucesso de cada uma dessas abordagens depende da compreensão global de todos os campos. Palavras-chave: Mulheres. Empoderamento feminino. Solução. Pobreza.